Adaptive diving depth control system for the drifting autonomous underwater vehicle - Viktor Ivel; Yuliya Gerasimova; Sayat Moldakhmetov; Makhabbat Krivolapova (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2025)
This article considers the system for controlling the diving depth of a drifting autonomous underwater vehicle (DAUV), which navigates underwater under the influence of sea currents in order to collect scientific information. The paper solves the problem of identifying non-stationary hydrodynamic parameters of the DAUV with the aim of adaptive adjustment of the DAUV control algorithm to increase the accuracy of bringing the DAUV to a given depth and minimizing the consumption of electricity consumed by power actuators. The solution to the problem is based on the use of parametric identification apparatus and adaptive control principles. The high quality of the DAUV diving depth control is achieved through the use of the method of adaptive adjustment of the parameters of the DAUV program model. The use of parametric identification of the hydrodynamic parameters of the DAUV made it possible to quickly adjust the corrective link in the control chain of the executing mechanism of the DAUV. The developed computer models and a set of semi-realistic tests made it possible to choose the most acceptable identification algorithm and configure the software implementation of the DAUV diving depth control law.